Analisis Kontribusi Pajak Negara dan Pajak Daerah terhadap Pendapatan Negara dan Kemandirian Fiskal Daerah di Indonesia - Suci Ramadhani; Rudi Sanjaya; Deni Husni Maulana; Kayla Nazwa Syabila (Jurnal Pajak dan Analisis Ekonomi Syariah, 2026)
This study aims to analyze the contribution of state and regional taxes to state revenue and regional fiscal independence in Indonesia. Taxes are the primary source of revenue used to finance governance and national and regional development. The study employed a qualitative descriptive method with a literature review approach and secondary data analysis derived from the State Budget (APBN) report, the Central Statistics Agency (BPS), and various scientific articles indexed by Sinta. The data were analyzed to identify the contribution of taxes to state revenue and the role of regional taxes in increasing Regional Original Income (PAD). The results show that tax revenue remains the largest source of state revenue, with dominant contributions coming from Income Tax (PPh) and Value Added Tax (PPN). Furthermore, regional taxes play a crucial role in enhancing regional fiscal capacity and supporting the implementation of regional autonomy. The effectiveness of tax management is influenced by the level of taxpayer compliance, the digitalization of tax administration, and the quality of government oversight. This study implies that optimizing the tax system through digital transformation and increasing public awareness can sustainably strengthen state and regional revenue.